Translating Muluki Ain of 1854 for Intercultural Communication in Law - Bhattarai, Achyutananda (JODEM: Journal of Language and Literature, 2024)
This paper attempts to explore intercultural communication in law through the legal translation of Muluki Ain of 1854 into English by applying Peter Newmark’s communicative translation approach. It tries to bridge the intercultural communication gap that exists between the source language (SL) and the target language (TL) readers. Communicating legal and cultural aspects of pre-modern Nepali life to the target reader is the primary objective of this research. It collects primary data from the SL book Muluki Ain of 1854 focusing on Hindu cultural provisions of Nepali native law. The data are presented, analyzed, and interpreted from the cultural aspects of the law of pre-modern Nepal. This research finds that the translating law of pre-modern Nepal contributes to communicating the Nepali indigenous legal system that was based on Hindu religious legal principles. The significance of this study is more to the comparative lawyers, legal translators, students of translation studies, and interested readers in translation. This research concludes that the translation of the Muluki Ain of 1854 has communicated the legal culture of pre-modern Nepal all over the world.